Expanding the applications of immune checkpoint inhibitors in advanced lung cancer beyond disease progression - Chen, Chao; Xiong, Xi; Cheng, Ying; Gen, Haiyun; Zhu, Wenqiang; Zhang, Fei; Zhu, Chuandong; Han, Siqi; Liu, Xiufeng (Frontiers in Immunology, 2023)
Background: Immunotherapy, particularly the utilization of immune checkpoint inhibitors (ICIs), assumes a pivotal role in the comprehensive management of advanced lung cancer. There has been substantial deliberation regarding the appropriateness of extending ICIs treatment beyond the point of disease progression. This study delves into the potential benefits of sustained utilization of ICIs subsequent to disease progression in patients.: A retrospective analysis was conducted on a cohort of 248 patients diagnosed with advanced lung cancer who received treatment with ICIs. The study population comprised 99 patients in the treatment beyond progression (TBP) group and 42 patients in the non-treatment beyond progression (NTBP) group. Parameters including progression-free survival (PFS), overall survival (OS), objective response rate (ORR), and disease control rate (DCR) were assessed. The Cox proportional hazard regression model was employed to analyze prognostic factors related to immunotherapy.Results: Patients undergoing primary treatment with PD-1/PD-L1 inhibitors exhibited a median progression-free survival (mPFS) of 5.3 months. In the context of disease progression, a comparison between the TBP and NTBP groups was performed with respect to mPFS. The results demonstrated that the TBP group manifested an mPFS of 8.6 months, contrasting with the NTBP group's mPFS of 4.0 months (p=0.028). The mean overall survival (mOS) in the TBP group exhibited a statistically significant increase in comparison to the NTBP group (14.1 months vs. 6.0 months, p=0.028). Evaluation of the objective response rate (ORR) between the TBP and NTBP groups revealed a substantial distinction. The TBP group displayed an ORR of 12.1%, while the NTBP group exhibited a lower ORR of 2.4%. The statistical analysis yielded a p-value of 0.068, signifying a notable trend towards significance. The disease control rate (DCR) was also assessed and exhibited a noteworthy variance between the two groups, with a higher DCR of 92.9% in contrast to 71.4% in the control group (p = 0.001).Subsequent to ICIs treatment, a subset of patients may derive continued benefits from anticancer therapy, notwithstanding the progression of their advanced lung cancer.